Analysis of soybean farmers response on Pajale Special Efforts Implementation (UPSUS) program. Issue 1 (April 2020) - Mahyuddin,; Saadah,; Darwis,; Lanuhu, N; Diansari, P; Anisa, A; Sulili, A; Wirdansyah, A
Abstract: Soybean self-sufficiency has been the main target of the government since 2015 along with two other food commodities, namely rice, and corn. The UPSUS Program (Special Effort) is an effort to support soy self-sufficiency. Special Efforts (UPSUS) is the Ministry of Agriculture's leading program to improve the welfare of farmers. With the UPSUS, it is expected that soybean production will increase. This study aims to determine the response of soybean farmers to the implementation of the Pajale Special Efforts (UPSUS) program. The population of the study was 150 farmers involved in the UPSUS Pajale Program taken by purposive sampling method. Analysis of the data used to determine farmers' responses to the Pajale Special Efforts (UPSUS) program was measured using a Likert scale and descriptive statistical analysis. The Likert scale used consists of the categories of very satisfied (5), satisfied (4), moderate (3), dissatisfied (2), very dissatisfied (1). The results of the study concluded that the response of farmers to the implementation of the Pajale Special Efforts Program (UPSUS) was included in the satisfied category (43%).